Teaching Trends in Virtual Education: An Interpretative Approach - Pando, Víctor F. (2018)
Based on the theoretical context of discussions about teaching trends in virtual education, particularly for higher education, this research develops an interpretation of some of these trends, resizing what was registered about it by other authors. To that end, a documentary study with an interpretativeanalytical approach was carried out. The results show that the Technological Didactics trend can be developed through the behavioral and connectivism theories, in which the dehumanization of the individual is concealed in teaching-learning processes of a technocentric nature, since in these processes, there are some virtualization threats and little attention to their main strengths. It was concluded that the impact of ICT deconstructs some expectations placed on them to improve the pedagogical task. In addition, it is recommended to address the Critical Didactics trend as a perspective of reflection on emerging pedagogies of the virtual environment.